2021
DOI: 10.1186/s43058-021-00154-5
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods evaluation of the large-scale implementation of a school- and community-based parenting program to reduce violence against children in Tanzania: a study protocol

Abstract: Background Despite the rapid dissemination of parenting programs aiming to reduce and prevent violence against children (VAC) worldwide, there is limited knowledge about and evidence of the implementation of these programs at scale. This study addresses this gap by assessing the quality of delivery and impact of an evidence-based parenting program for parents/caregivers and their adolescent girls aged 9 to 14—Parenting for Lifelong Health Teens (PLH-Teens), known locally as Furaha Teens—on redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The in-person PLH Teens programme (locally known in Tanzania as Furaha Teens ) was successfully delivered to 75,061 Tanzanian caregivers and children with promising positive impact in a large-scale pre-post evaluation, including reduced child maltreatment, improved family relationships, promoted child development, and reduced IPV perpetration and experience [ 39 ]. The Tanzanian-adapted version of PLH Teens also demonstrated high cultural acceptability and programme fidelity when delivered at scale.…”
Section: Introductionmentioning
confidence: 99%
“…The in-person PLH Teens programme (locally known in Tanzania as Furaha Teens ) was successfully delivered to 75,061 Tanzanian caregivers and children with promising positive impact in a large-scale pre-post evaluation, including reduced child maltreatment, improved family relationships, promoted child development, and reduced IPV perpetration and experience [ 39 ]. The Tanzanian-adapted version of PLH Teens also demonstrated high cultural acceptability and programme fidelity when delivered at scale.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found improved positive parenting and child behaviour, while reducing family violence. Further information about PLH and its growing evidence base is available in numerous published papers, protocols, and resources (e.g., Martin, Lachman, et al, 2021 ; Shenderovich et al, 2020 ; World Health Organisation [WHO], 2020 ). As the evidence supporting parenting programmes such as PLH is positive and substantial, studying their implementation fidelity represents an important way to explore which programme elements are correlated with outcomes and how to improve delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigators have examined the prevalence, context, and health outcomes of VAC (Vagi et al, 2016), its impact (Hillis et al, 2017), possible remedies (Lachman et al, 2020;Martin et al, 2021), and existing interventions (Reuben et al, 2022;Wangamati et al, 2022). Although some research has been carried out on community-based child protection mechanisms in Tanzania (e.g., Reuben et al, 2022), there is still limited understanding of the dynamics of civil society networks and connections at different levels as well as the advantages of networks, and the challenges they face, in regard to VAC prevention and response.…”
mentioning
confidence: 99%